2019
DOI: 10.4067/s0718-221x2019005000206
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of novel wood-based reinforced composites manufactured from crushed veneers and phenolic resins

Abstract: This study was performed to determine the surface properties of novel wood-based reinforced composites made from poplar veneers and phenolic resins. The veneers with different thickness (1,8; 4; 6; 8 mm) were finely crushed and then were impregnated with phenolic resins to achieve different resin loading (12, 14, 18%). Finally, they were laminated or random paved to manufacture novel wood-based reinforced composites with different target densities (900-1100 kg/m 3). With increased veneer thickness or resin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Fluffed bamboo [1,8] and wood [2,5] veneers were prepared according to the methods detailed in previously published literature. Specifically, the Neosinocalamus affinis bamboo culm was processed into two 2000 mm long semicircular bamboo bundles by transverse truncation and longitudinal splitting.…”
Section: Preparation Of Bamboo and Wood Fluffed Veneersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluffed bamboo [1,8] and wood [2,5] veneers were prepared according to the methods detailed in previously published literature. Specifically, the Neosinocalamus affinis bamboo culm was processed into two 2000 mm long semicircular bamboo bundles by transverse truncation and longitudinal splitting.…”
Section: Preparation Of Bamboo and Wood Fluffed Veneersmentioning
confidence: 99%
“…Furthermore, compared with a traditional poplar WLC fabricated using veneers without fluffing, a novel WLC constructed using fluffed veneers exhibited a slight decline in mechanical strength but significantly improved dimensional stability [4]. Additionally, denser WLCs have been observed to exhibited improvements in mechanical properties, dimensional stability, and surface properties [2,4,5]. Finally, the veneer thickness, mat formation, and resin solid content have also been found to have an important impact on the physical and mechanical properties of WLCs [6].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, it can be said that the increase in the contact angle values of the impregnated specimens is due to the decrease in the roughness values of these specimens and the hydrophobic (water repellent) nature of the impregnation materials used. Huang et al (2019) reported that the density increase in poplar veneers laminated after impregnation with phenolic resins has a reducing effect on the surface roughness and there is also a negative correlation between contact angle and surface roughness. Poplar wood treated with monomers synthesized from styrene and methyl methacrylate has a higher contact angle than untreated poplar (Li et al 2013).…”
Section: Fig 2 Roughness Values Of Impregnated and Densified Wood Spe...mentioning
confidence: 99%
“…The roughness or wettability characteristics of wood surfaces are separately affected by many factors, such as the wood anatomical properties, density, moisture, compression parameters, and properties of the machining process (Kılıç et al 2006;Diouf et al 2011;Ünsal et al 2011;Arruda and Del Menezzi 2013;Sofuoǧlu and Kurtoğlu 2015;Bekhta and Krystofiak 2016;Bekhta et al 2017;İlçe 2018;Pinkowski et al 2018). In addition, surface roughness significantly affects the equilibrium and nonequilibrium contact angles of solid materials (Shupe et al 2001;Büyüksarı et al 2011;Akgül et al 2012;Papp and Csiha 2017;Huang et al 2019;Luo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness has a great influence on contact angle values. Surface roughness causes a hydrophilic surface to be more hydrophilic, and a hydrophobic surface to be more hydrophobic [19,20]. The surface of natural wood, for example, is hydrophilic, and high surface roughness creates a more hydrophilic surface [21].…”
Section: Introductionmentioning
confidence: 99%